Control of systemic inflammation through early nitric oxide supplementation with nitric oxide releasing nanoparticles - Williams, Alexander T. (Free Radic Biol Med, 2020)
Amelioration of immune overactivity during sepsis is key to restoring hemodynamics, microvascular blood flow, and tissue oxygenation, and in preventing multi-organ dysfunction syndrome. The systemic inflammatory response syndrome that results from sepsis ultimately leads to degradation of the endothelial glycocalyx and subsequently increased vascular leakage. Current fluid resuscitation techniques only transiently improve outcomes in sepsis, and can cause edema. Nitric oxide (NO) treatment for sepsis has shown promise in the past, but implementation is difficult due to the challenges associated with delivery and the transient nature of NO. To address this, we tested the anti-inflammatory efficacy of sustained delivery of exogenous NO using i.v. infused NO releasing nanoparticles (NO-np). The impact of NO-np on microhemodynamics and immune response in a lipopolysaccharide (LPS) induced endotoxemia mouse model was evaluated. NO-np treatment significantly attenuated the pro-inflammatory response by promoting M2 macrophage repolarization, which reduced the presence of pro-inflammatory cytokines in the serum and slowed vascular extravasation. Combined, this resulted in significantly improved microvascular blood flow and 72-h survival of animals treated with NO-np. The results from this study suggest that sustained supplementation of endogenous NO ameliorates and may prevent the morbidities of acute systemic inflammatory conditions. Given that endothelial dysfunction is a common denominator in many acute inflammatory conditions, it is likely that NO enhancement strategies may be useful for the treatment of sepsis and other acute inflammatory insults that trigger severe systemic pro-inflammatory responses and often result in a cytokine storm, as seen in COVID-19.